KEBIJAKAN ANGGARAN PEMERINTAH DAERAH: STUDI KASUS DI JAWA TENGAH - Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
In local government, budgeting is an important activity that indicates the level of decentralization. It shows a real commitment of local governments to achieve the purpose of improving people's welfare and public services. The purpose of this study is to analyze the structure of budgetary expenditure and revenue (APBD) to determine the priority of regional policy in Central Java for its functions. The method of this study was descriptive qualitative. This study concluded that the local government budget is still heavily dependent on central government, and budget structure to better reflect priorities compliance accounting system and rigid management of public finances, more elite-oriented than the increase in social welfare and public services